Medication Errors in a Private Hospital of Bangladesh (Bangladesh Pharmaceutical Journal, 2015)
The present study was designed to assess the incidence of various prescription errors with handwritten prescription order for hospitalized patients. Investigation was made in a private hospital situated at the outskirts of Bogra, Bangladesh. A total of 200 prescription orders for the admitted patients in medicine, surgery, orthopedic and diabetes ward of the hospital were evaluated. Prescribing errors were determined by consulting with the standard treatment guidelines, text books and authentic online sources. About 692 (3.46 per prescription) medication related problems (MRPs) were identified from 1234 prescribed drugs. The names of 63 prescribed drugs were not clear due to ambiguous hand writing, the dose strength were found missing for 219 drugs and surprisingly among them 42 drugs were available in the market in multiple dose strengths. More importantly, a total of 366 drug interactions were also identified of which 12.57% was serious, 53.28% was significant and 34.15% was minor. About 15% prescriptions orders were identified for the patients with kidney and urinary problems and there were no dose adjustment. In 3% of prescriptions, two drugs having same pharmacological action were prescribed. Although in medical practice single drug prescription is encouraged, the average number of prescribed drugs per prescription was 6.17. These serious prescription errors are the major cause of patient morbidity and mortality, increased length of hospital stay and substantial extra treatment costs. DOI: http://dx.doi.org/10.3329/bpj.v17i1.22311 Bangladesh Pharmaceutical Journal 17(1): 32-37, 2014